Transition metal dichalcogenides-based catalysts for CO2 conversion: An updated review - Khaidar D.M.; Isahak W.N.R.W.; Ramli Z.A.C.; Ahmad K.N. (Elsevier Ltd, 2025)
The rapid depletion of fossil fuels has become the worst scenario as most of the energy needed still depends on the use of fossil energy, oil, natural gas, and coal. The combustion of crude oil and coal has contributed to the major anthropogenic carbon dioxide (CO2) gas in the atmosphere and has worsened climate change and global warming. Therefore, the abundant CO2 in the surrounding has opened the door to many studies to convert CO2 into the next generation of fuels and indirectly reduce the greenhouse effect. Transition metal dichalcogenides (TMDs) nanomaterials have appeared as a practical and reliable catalyst for CO2 conversion to sustainable fuels under normal atmospheric conditions. Having fascinating electronic and catalytic properties, these earth-abundant element-based materials are being explored and developed for real-world application. This paper reviews the recent insight into the synthesis, properties and application of TMDs as catalysts in electrocatalysis, photocatalysis and thermal catalysis for CO2 reduction and conversion. The role of type of sulfide (S), selenide (Se) and telluride (Te)-based TMDs in the production of various valuable products such as formate (HCO2?), formic acid (CH2O2), methanol (CH3OH), and ethanol (CH3CH2OH), amongst others, will be discussed in detail. The possible reaction pathways and mechanisms and the relationship between tailoring the catalysts properties and CO2 activation towards high CO2 reduction and conversion efficiency will also be evaluated. ? 2024 Hydrogen Energy Publications LLC